Consortium of Plant Growth-Promoting Rhizobacteria Strains Suppresses Sweet Pepper Disease by Altering the Rhizosphere Microbiota - Zhang, Li-Na; Wang, Da-Cheng; Hu, Qiang; Dai, Xiang-Qun; Xie, Yue-Sheng; Li, Qing; Liu, Hua-Mei; Guo, Jian-Hua (Frontiers in Microbiology, 2019)
Beneficial microorganisms have been used extensively to make plants more resistant to abiotic and biotic stress. We previously identified a consortium of three plant growth-promoting rhizobacteria (PGPR) strains (Bacillus cereus AR156, Bacillus subtilis SM21, and Serratia sp. XY21; hereafter “BBS”) as a promising and environmentally friendly biocontrol agent. In this study, the effect of BBS on a soil-borne disease of sweet pepper was evaluated. Application of BBS significantly reduced the prevalence of phytophthora blight and improved fruit quality and soil properties relative to the control. BBS was able to alter the soil bacterial community: it significantly increased the abundances of Burkholderia, Comamonas, and Ramlibacter, which were negatively associated with disease severity, relative to the control. Redundancy analysis suggested that BBS-treated soil samples were dominated by Burkholderia, Comamonas, Ramlibacter, Sporichthya, Achromobacter and Pontibacter; abundance of these genera was related to total organic carbon (TOC), total nitrogen (TN), ammonium nitrogen (AN), total potassium (TP) and available phosphorus (AP) contents. This suggests that BBS treatment shifted the microbe community to one that suppressed soil-borne disease and improved the soil chemical properties.